The novel SLC40A1 (T419I) variant results in a loss-of-function phenotype and may provide insights into the mechanism of large granular lymphocytic leukemia and pure red cell aplasia. Issue 1 (6th January 2022) - Wu, Hongfei; Ren, Xiang; Ge, Meili; Dong, Peiyuan; Wang, Shichong; Yi, Huiming; Li, Xingxin; Huo, Jiali; Zheng, Xuan; Gao, Mengying; Huang, Jinbo; Zhang, Jing; et al.
Abstract : Abstract: Variants in the solute carrier family 40 member 1 (SLC40A1) gene are the molecular basis of ferroportin disease, which is an autosomal dominant hereditary hemochromatosis. Here, we present a patient with pure red cell aplasia (PRCA) and large granular lymphocytic leukemia (LGLL) associated with an extremely high levels of serum ferritin and iron overload syndrome. Whole exon sequencing revealed a novel heterozygous variant in SLC40A1 (p.T419I), which was found in his daughter as well. A series of functional studies in vitro of the T419I variant in ferroportin were conducted and the results revealed a reduced capacity of iron export from cells without changes in protein localization and its sensitivity to hepcidin. Intracellular iron storage in mutated cells was significantly higher than that of wild-type. These findings suggest that the novel variant p.T419I can cause the classical form of ferroportin disease and an elevated intracellular iron level indicates a potential novel pathogenic mechanism underlying PRCA and LGLL.